Increasingly structuring research from Africa on the relationship between Information and Communication Technologies and social change in the 3rd millennium - (:unkn) unknown (My University, 2020)
The African continent may have appeared left behind in the movement of emergence and development of information and communication techniques. However, research in Africa, by Africa, on Africa, is proving increasingly structuring, beyond the first monographic approaches which already go beyond certain contributions, even if the latter are still too rare, embryonic and still insufficiently referenced. This production of knowledge must therefore work to further assert its visibility. Especially since beyond academic circles, the analyzes proposed in the heat of the moment by the producers of media information reveal a widely criticized technological determinism in CIS, which discouragingly thwarts the understanding of the role played by ICT and social media in social change.
Keywords: African Research